CLINICAL AND ANAMNESTIC FEATURES OF THE COURSE OF ALLERGIC DISEASES IN ADOLESCENCE AND YOUNG ADULTHOOD - Абдурахманов К. Х.; Файзимуродов А. С.; Мирзаханов А. А. (Web of Journals Publishing, 2025)
In school-age children, the presence of concomitant diseases made it difficult to diagnose AD in a timely manner: we found that children with perinatal damage to the central nervous system and intestinal dysbiosis were diagnosed more recently. Frequent exacerbations of the disease contributed to the earlier and timely diagnosis of AD.
Keywords: Bronchial asthma, age, children, peculiarity